Determinants of Technological and non-technological Innovations: Evidence from Ghana' Manufacturing and Service Sectors - Odei, Samuel Amponsah; Odei, Michael Amponsah; Toseafa, Evelyn (Routledge, 2023)
This paper aims at investigating the various factors driving technological and non-technological innovations in the manufacturing and service sectors in Ghana. We argue that numerous previous studies have shown that digitalization, firms' collaborations, access to finance, engaging in research and development and certain firm characteristic such as age, size and ownership influence firms' aptitude and incentives to be innovative. However, in the context of developing countries like Ghana, we do not know whether these same determinants also have positive effects on stimulating innovations at the firm-level. Using a sample of 549 firms sourced from the World Bank Enterprises Survey conducted between 2007 and 2013, this study finds that the adoption of digitalization promotes non-technological (organizational) innovations than technological innovations. We also find that firms' innovation collaboration with consultants and universities rather exert no impact on technological and non-technological innovations. Our finding show that internal R&D enhance technological innovations and not non-technological innovations. The main practical implications of the study are that attempts to boosting firm-level and developing countries innovation potentials should mainly focus on improving internal R&D and innovation support activities, expanding access to finance, and upgrading Information and Communication Technology (ICT) infrastructure to enhance digitalization.
Determinanty technologických a netechnologických inovací: Důkazy z ghanských výrobních odvětví a odvětví služeb
Keywords: Technological innovation; non-technological innovation; innovation collaboration; digitalization; research and development; R&D funding; Ghana; Technologické inovace; netechnologické inovace; inovační spolupráce; digitalizace; výzkum a vývoj; financování výzkumu a vývoje; Ghana